Multi-Parameter Cell Affinity Chromatography: Separation and Analysis in a Single Microfluidic Channel - Li, Peng (2012)
The ability to sort and capture more than one cell type from a complex sample will enable a wide variety of studies of cell proliferation, death, and the analysis of disease states. In this work, we integrated a pneumatic actuated control layer to an affinity separation layer to create different antibody coating regions on the same fluidic channel. The comparison of different antibody capture capabilities to the same cell line was demonstrated by flowing Ramos cells through anti-CD19 and anti-CD71 coated regions in the same channel, respectively. It was determined that cell capture density on anti-CD19 region was 2.44±0.13 times higher than on anti-CD71 coated region. This approach can be used to test different affinity molecules for selectivity and capture efficiency using a single cell line in one separation. Selective capture of Ramos and HuT 78 cells from a mixture was also demonstrated using two antibody regions in the same channel. Greater than 90% purity was obtained on both capture areas in both continuous flow and stop flow separation modes. A four-region antibody coated device was then fabricated to study the simultaneous, serial capture of three different cell lines. In this case the device showed effective capture of cells in a single separation channel, opening up the possibility of multiple cell sorting. Multi-parameter sequential blood sample analysis was also demonstrated with high capture specificity (>97% for both CD19+ and CD4+ leukocytes). The chip can also be used to selectively treat cells after affinity separation.